Success of referring participants to the Generation program and lessons learned for future enrollment into Alzheimer's disease prevention trials: Human: Improving clinical trial methodology. (7th December 2020) - Gordon, David; Salata, Hayley; Walsh, Trisha L.; High, Nellie M.; Kettenhoven, Cassandra L.; Reiman, Eric M.; Tariot, Pierre N.; Langbaum, Jessica B.
Abstract: Background: We developed GeneMatch in 2015 to assist enrollment into Alzheimer's disease (AD) prevention studies by enriching referrals based in part on APOE4 genotype. The API Generation Program, which enrolled cognitively unimpaired (CU) APOE4 carriers ages 60‐75 was the first multisite clinical trial to use GeneMatch as a recruitment source. Method: GeneMatch is a US‐based, trial‐independent recruitment program of the Alzheimer's Prevention Registry (APR), conducting APOE testing in CU individuals aged 55‐75. GeneMatch does not disclose APOE results to participants directly, however, results are used to match participants to enrolling studies in a manner that does not inadvertently disclose genotype. Participants are notified by email when they have been invited to a study. A reminder email is sent 7 days later, a letter is mailed to the participant's home 2mo after if no response is received. Once a participant accepts his/her invitation, their contact information is shared with their preferred study site through an online portal. In July 2016, GeneMatch began inviting participants to the Generation Program. Result: To date, >90, 000 people have joined GeneMatch, > 30% are APOE4 carriers. Recruitment in the Generation Program and treatment with umibecestat was terminated in July 2019 after an early signal of mild worsening in some measures of cognitive function. At that time, 16, 521 GeneMatch participants had been invited to the Generation Program, 33% (5, 461) of whom accepted their invitations. Of those who accepted, 2, 202 consented to the Generation Program (randomization data not yet available), 292 were scheduled for screening, 511 were awaiting scheduling for screening, 242 were waiting to be contacted by their selected study site, 1, 209 were found to be ineligible after a phone screen by sites, 695 were no longer interested, and 310 were lost to follow‐up. Conclusion: The Generation Program was on track to complete enrollment in 2019 and GeneMatch was a successful program in helping to recruit APOE4 carriers. Lessons learned include the importance for GeneMatch to coordinate with study sites to ensure they are prepared to receive referrals Future analyses will examine success of GeneMatch (vs. other recruitment sources) for randomization.